Evolution of international carbon markets: lessons for the Paris Agreement. (16th August 2019) - Michaelowa, Axel; Shishlov, Igor; Brescia, Dario
Abstract: The Paris Agreement will greatly benefit from the past experience with international market mechanisms for greenhouse gas (GHG) emissions reductions and related regulatory systems, which have gone through four periods with specific challenges. The first period 1997–2004 operationalized the mechanisms defined in the Kyoto Protocol, the Clean Development Mechanism (CDM) and Joint Implementation (JI). Pilot activities in different sectors were undertaken by the public sector, and the first baseline and monitoring methodologies officially approved. Between 2005 and 2011, the carbon markets expanded massively. The EU emission trading scheme (EU ETS) was linked to the Kyoto mechanisms, creating demand for carbon credits from the private sector. During this "gold rush" period criticism emerged with regarding the uneven geographical distribution of projects, as well as environmental integrity problems related to baselines and additionality. The next period saw a collapse in carbon prices between 2012 and 2014, limiting the development of new projects. The quantitative limits on the use of offsets in the EU ETS were reached and the failure to agree on a new international regime resulted in a drying up of demand from governments. The 2015–2018 period is characterized by a gradual stabilization of the international climate regime. The Paris Agreement adopted in 2015 increases complexity through global participation in mitigation. Future carbon markets will therefore face both old challenges—supply–demand balance, environmental integrity, transaction costs—and new ones—interactions with other policies and national targets, and sectoral/policy baselines and additionality checks preventing hot air proliferation. This article is categorized under: The Carbon Economy and Climate Mitigation > Policies, Instruments, Lifestyles, Behavior Abstract : The roller coaster ride of international carbon market mechanisms over the last 20 years has four phases, ranging from exuberance (2005–2011) to hibernation (2012–2014), determined by changes in public and private demand for carbon credits and the varying ability of regulators to credibly operationalize the mechanisms.